Kajian Literatur Sistematis: Skema Pengendalian Biaya dalam Asuransi Kesehatan Nasional di Beberapa Negara - Pujiyanti, Eka; Setiawan, Ery; Sari, Euis Ratna; Suwandi, Indah Pratiwi (Jurnal Ekonomi Kesehatan Indonesia, 2019)
Cost-containment is one of several strategies to ensure the financial sustainability of the National Health Insurance scheme. Several cost-containment models were commonly globally, such as cost-sharing, capping, and others. This review aims to determine the costs and impacts of implemented policy schemes as cost-containment instruments in various countries. We performed a systematic review from several primary databases (Proquest, Pubmed, and Cochrane Library) with the primary intervention are the cost-sharing methods. The results of our review focused on the cost containment scheme from the government perspective, in which the context of social insurance can be a modification of payment systems, cost-sharing, capping/quota, and waiting period. From one of the studies in Canada, we can see that the result has a significant impact on the health system, reducing the expenditure and the use of drugs that are not essential, and also indirectly improve the technical efficiency of the drug market through the care of participants in drug utilisation. In this research, it can be concluded that the implementation of cost containment schemes can reduce the moral hazard risk from the perspective of participants with additional contributions to the utilisation of healthcare services.